Younger children in ECEC: focus on the national steering documents in the Nordic countries. Issue 6 (2nd June 2016) - Hännikäinen, Maritta
Abstract : The aim of this study was to review the national steering documents on early childhood education and care (ECEC) in Denmark, Finland, Iceland, Norway and Sweden, with the focus on children up to the age of three, posing the question: What do these documents tell us about ECEC for younger children in the Nordic early childhood settings? Methodologically, a qualitative document analysis was applied. The documents provide a picture of young children whose age, individual needs and a number of other factors, such as cultural background, should be taken into account in ECEC. These children learn holistically, in close interaction with their environment. Their safety and well-being are seen as paramount. The physical and social worlds of children expand with the help of experienced and sensitive educators. However, younger children are rarely addressed specifically in these documents. For instance, many important themes, such as the very beginning of the child's attendance in ECEC, are poorly explicated in them.